From Virtual Experience to Real Action: Efficiency–Flexibility Ambidexterity Fuels Virtual Reality Webrooming Behavior - Zhi-Tao Chen; Guicheng Shi; Yu-Hao Zheng (Journal of Theoretical and Applied Electronic Commerce Research, 2025)
In the post-digital era, virtual reality (VR) technology is increasingly being utilized in the real estate industry. In this study, the influence of functional experience with VR technology (e.g., interactivity and flexibility) on consumers’ offline house viewing intentions is explored. On the basis of efficiency–flexibility ambidexterity and customer inspiration theory, a structural equation model was employed to analyze empirical data collected from 388 consumers in the Guangdong–Hong Kong–Macao Greater Bay Area. The key findings are as follows: (1) VR technology features have significant positive effects on customer inspiration, which in turn enhances customers’ willingness to view houses offline; (2) VR presence, enjoyment, interactivity, and flexibility all contribute to customer inspiration, with VR presence having the most substantial impact; and (3) VR knowledge and consumer demand for uniqueness significantly moderate the relationship between VR technology features and customer inspiration. For example, consumers with substantial VR knowledge can more effectively leverage VR technology, whereas those with a strong need for uniqueness are more likely to be inspired by the innovative aspects of VR. This research provides theoretical support for the application of VR technology in real estate marketing and practical guidance for enterprises to optimize VR marketing strategies, improve consumer experiences, and drive offline transactions. These insights can help companies better understand consumer psychology and behaviour in the digital marketing landscape.